2007
DOI: 10.1103/physrevb.75.132503
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the tunneling spectroscopy of ferromagnetic superconductors

Abstract: We study tunneling conductance in normal metal / insulator / ferromagnetic superconductor junctions. The tunneling spectra show a clear difference between spin-singlet s-wave pairing, spintriplet opposite spin pairing and spin-triplet equal spin pairing: These pairings exhibit, respectively, gap struture, double peak structure and zero bias peak in the spectra. The obtained result may serve as a tool for determining the pairing symmetry of ferromagnetic superconductors.Magnetism and superconductivity have been… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 36 publications
3
103
0
Order By: Relevance
“…This is because the increase of exchange fields decreases Andreev reflection coefficient and the Josephson current. Also, as it is mentioned in [23,24], the wave functions of P wave in antiparallel case depend on exchange field. Comparing Figs.…”
Section: Results and Conclusionmentioning
confidence: 93%
See 2 more Smart Citations
“…This is because the increase of exchange fields decreases Andreev reflection coefficient and the Josephson current. Also, as it is mentioned in [23,24], the wave functions of P wave in antiparallel case depend on exchange field. Comparing Figs.…”
Section: Results and Conclusionmentioning
confidence: 93%
“…3a, b that Josephson current does not depend on exchange field. This is due to the fact that the wave functions in the case of parallel P wave symmetry do not depend on exchange fields [23,24]. In order to discuss with more details, we obtain Josephson current from (5) which is as follows:…”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The homogeneous spin splitting in the superconductor can be realized in the systems such as thin F/S junctions [9,10] or thin superconductor films under the application of an in-plane magnetic field [11]. It has been shown that N/ZS junctions, where N stands for a normal metal, can generate highly spin-polarized current [12][13][14][15]. Josephson junctions with spin-split superconductors have been also studied in various types of structures.…”
Section: Introductionmentioning
confidence: 99%
“…The homogeneous spin splitting in the superconductor can be realized in the systems such as thin F/S junctions [200,201] or thin superconductor films under the application of an in-plane magnetic field [202]. It has been shown that N/ZS junctions, where N stands for a normal metal, can generate highly spin-polarized current [203][204][205][206]. Josephson junctions with spin-split superconductors have been also studied in various types of structures.…”
Section: Introductionmentioning
confidence: 99%